A preliminary study of the safety and effectiveness of isoproterenol loading transesophageal echocardiography in atrial fibrillation. (4th February 2022) - Takahashi, T; Kusunose, K; Hayashi, S; Yamaguchi, N; Morita, S; Hirata, Y; Nishio, S; Okushi, Y; Seno, H; Saijo, Y; Yamada, H; Sata, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In patients with sludge or severe spontaneous echo contrast (SEC) in the left atrial appendage (LAA), isoproterenol loading transesophageal echocardiography (ISP-TEE) has been reported to check the presence of thrombus in the LAA, as the sludge or severe SEC disappears (Figure 1). Purpose: The aim of this study was to assess the safety of ISP-TEE for the identification of LAA thrombus and the hemodynamic changes in the LAA caused by ISP loading. Methods: We prospectively enrolled 25 patients with atrial fibrillation (AF) and sludge or SEC in the LAA who underwent ISP-TEE from April 2020 to July 2021. ISP was administered intravenously to achieve the target heart rate (HR) defined as follows: Max HR [beats per minutes: bpm] = 220 – age (years), Target HR [bpm] = Max HR × 0.8. Patients with tachycardia exceeding Max HR before ISP administration, hemodynamic instability, and other contraindications to ISP were excluded from the study. To assess the safety of ISP-TEE, we evaluated patients' condition, changes in systolic blood pressure (sBP) and HR before and after ISP loading. We also assessed the presence or absence of worsening heart failure, new arrhythmias other than atrial fibrillation, and cerebral infarction or transient ischemic attack during the examination, and after 24 hours. Hemodynamic evaluation was performed using LAA blood flow velocity, LAA tissue Doppler imaging (TDI) velocity, and LAA volume fraction (LAAVF) defined as follows: LAAVF (%) = (Max LAA volume – Min LAA volume) / Max LAA volume × 100. Quantification of LAA volume was performed using the stacked-contour method of a 3-dimensional TEE full-volume acquisition. Results: Among 25 patients, 13 patients had sludge or grade3 SEC, 7 patients had grade2 SEC, 5 patients had grade1 SEC. HR after ISP loading was significantly higher than before loading, but sBP did not change significantly before and after ISP loading. No complications due to ISP loading were observed during examination and after 24 hours. After ISP loading, there were 18 patients with grade 1 SEC or no SEC (classified as Group1), 7 patients had residual sludge or grade 2 to 3 SEC (classified as Group2). The differences in LAA blood flow velocity between before and after ISP loading was faster in Group1 than in Group2: 13.0 ± 10.5 vs 2.6 ± 4.2. p = 0.019. The differences in TDI velocity was also faster in Group1 than in Group2: 1.46 ± 1.14 vs 0.19 ± 0.50, p = 0.010. The differences in LAAVF was higher in Group1 than in Group2: 13.7 ± 10.3 vs 2.2 ± 2.0, p = 0.009. Conclusions: In our study, no complications were observed in ISP-TEE for the identification of LAA thrombus. Patients with grade 1 SEC or no SEC, the LAA function was increased by ISP loading. These results may provide insights into the mechanisms of ISP loading on SEC in the LAA.